Portable Battery for Marine Leisure - Bolminger, Erik; Palm, Gustav; Strömdahl, Evelina; Sundqvist, Tinnie (My University, 2022)
Electrification is one of the biggest disruptive trends within the marine leisure sector. It follows a similar path as the automotive industry. One of the major challenges is the availability of charging. Many marinas do not have sufficient shore power for the charging of large batteries and if electrification is to succeed, more options for customers interested in electric boating is needed. One alternative this report concluded is the possibility to develop a portable battery swapping system where a sailboat owner could swap the discharged battery for a fully charged one via a swapping mechanism. This would allow a third party to own a limited number of standardized batteries for electromobility customers and charge the batteries slowly to avoid an excessive load on the power grid. The methodology was firmly based on a project design and development process. An extensive study was conducted on the customers and the behavior of sailboat users in order to develop target specifications, needs and requirements for developing a portable battery swapping system. Meanwhile, the team partook in literature studies, contacting boat manufacturers and visiting different boatyards. The customer research was based on a quantitative and qualitative study through both a survey and deeper interviews that was answered in total by 187 sailboat users. With this solid foundation, concepts where generated and eliminated until a single concept was further developed and investigated. The concept that was further developed resulted in a battery swapping system by function sharing with already existing equipment on the boat. The batteries where placed behind the staircase of the sailboat, where the conventional combustion engine many times is placed, and a hatch just above this position was implemented. The boom in co-operation with a pulley system is used to lift the batteries and swing it out over the docks. The same procedure in reverse is applied for reloading fully charged batteries onto the sailboat. Lithium-Ion was the chosen material for the battery because of the lightness of their building components, high loading capacity and longer cycle life. The business case for this is based on a subscription model where the sailboat owners subscribe on a wanted amount of batteries. The swapping stations are planned to be as self-sustaining as possible, just like an unmanned fuel station. A third part stakeholder operates the swapping stations by making sure there is enough batteries to meet the demands, doing maintenance and providing the location where the batteries can be placed. The project resulted in a model for a battery swapping system, complete with example modules and mechanical assistance to handle them. The concept allows sailboat users to maintain their current use of functions and equipment except for ways of heating the water and the cabin, which needs to be further researched if the project is to be continued.